Institutional and educational provisions for sport reserve training service at research education center "Success Academy" - Kadakin, V. V.; Chetaikina, O. V.; Kulebyakina, M. Yu.; Yakimova, E. A. (Theory and Practice of Physical Culture, 2018)
Competition on the global sport arenas has been on the rise for the last decade, and this is the reason why the Russian sport system needs to modernize the sport training and excellence systems with a special priority to the junior prospects` selection process and the institutional development initiatives to ensure progress and inflow of the human resource in the sector. The gifted children and youth selection mission shall be facilitated by a closer cooperation of schools and universities with their material, technical, human, programmatic and practical resources being united and fully mobilized for success. This was the key argument for establishing the `Success Academy` Research Education Center at Mordovian State Pedagogical Institute (MSPI) named after M.E. Evsevyev with support from the Ministry of Education and Science of the Russian Federation, Mordovian Republican Government and `Sirius` Education Center in Sochi. Subject to analysis in the article is the MSPI progress in implementing a few general education programs at the `Success Academy` REC for the junior prospects having good chances for a competitive progress. The study spells out the key institutional and educational provisions for success of the sport reserve training service.